IMPROVEMENT IN BENEFICIATION OF Low GRADE FLUORITE ORE FROM KALAT MARAN RANGE (Biological Sciences - PJSIR, 2002)
This paper describes a bench scale investigation on the preparation of metallurgical  and  chemical  grade  fluorspar  concentrate from a low-grade fluorite ore from Kalat Maran Range. A combination of chemical treatment and flotation techniques has been applied to fluorite ore. The ore initially containing 36.5% calcium fluoride has been processed and benefic1ated  to produce  calcium  fluoride concentrate  containing  98.7%  calcium  fluoride with  99.8%   recovery.